Corruption in Action in an Emerging Democracy: The Case of Socio-Pragmatic Metaphors in Cameroon English Usage - Tamfuh, Willie Mushing (International Journal of Linguistics, 2021)
In recent times, the Cameroon society has witnessed a decline in social and moral values, which has greatly influenced people’s use of language. Over the years, English has equally witnessed a degradation of the language to such an extent that one can talk of corrupt language. Corruption is a key subject that has gained the keen attention of political and social scientists as it affects the political, economic, social and cultural life of a society. This paper sets to identify the systems or rules and conventions according to which the language of corruption operates and concerns the semantic description of the typical words and expressions Cameroonians use to denote this practice in contemporary Cameroon. The idea is that the language we use is a reflection of the society in which we live and a representation of the social reality. This investigation aims to identify, collect and analyse specimens of utterances characteristic of corruption vocabulary and to describe this form of language use from a socio-pragmatic perspective. The scope of study is limited to establish a relationship between people, the language and a complex multilingual society as Cameroon. Data was collected from both oral and written sources as a representation of the opinions gathered from a cross section of Cameroonians. The significance of our study lies in the linguistic description of some characteristic of corruption related discourse. Using the participant observation, both spoken and written data were collected from different sources from the vantage point of functional lexicology and cognitive linguistics. A combination of different known theories, notably; the variation theory, speech act theory, lexico-semantics and the Pragmatic theory relevant to describe an utterance as a speech forms capable of a communicative performative action. Findings reveal that corruption is ubiquitous, corrosive and a dishonest deviant behaviour that severely damages personal and national reputation. To counter this, those engaged in the practice use different speech features such as borrowings, coinages, synonyms, clichés, metaphors and euphemisms. Metaphors and euphemisms are indirect ways speakers communicate important information. The language of corruption is strikingly similar in its soothing, euphemistic tone. Inadvertently, as language users have developed myriads of indirect and camouflage ways to refer to corruption, the language of corruption is also developing its own lexicon and linguistic features.